Prevalence of Urinary Tract Infection due to Urinary Catheterization in Obstetric and Gynaecological Operations - Akter, Jesmin; Seraji, Ahmad; Nahar, Lutfun; Khan, Shahriar Islam; Ahsanullah, Md Redwan (Bangladesh Journal of Medical Science, 2019)
Background: Urinary catheterization is routinely done in major gynaecological and obstetric operations in our country. It has some advantages and disadvantages of its own. Among the advantages, it can significantly prevent retention of urine, help in measuring urinary output, avoid discomfort due to full bladder, prevent postpartum hemorrhage and reduce spinal headache due to reduced movements. On the other hand, it can be a constant source of urethral irritation leading to UTI and can cause urethral strictures. So, a quantitative research is necessary to determine the relationship between urinary catheterization and UTI, for establishing a guideline for judicious catheterization. Methods: Between January 2010 and December 2011, data was collected for conducting an cross-sectional observational study on 49 subjects undergoing various gynaecological and obstetric operations. Precatheterization urine for routine and culture-sensitivity findings were recorded and compared with catheter tip culture and sensitivity after removal. Besides, other factors e.g. clinical history, comorbidity status, hemoglobin status, duration of catheterization, nature of operation etc was brought into consideration. Results: Patients having urinary catheters for more than 5 days, were found to be more than twice as likely to be developing UTI in various operations, than the patients having catheter for one day. Preoperative albuminuria was also found to be a likely predisposing factor, as the percentage of patients with UTI who had preoperative albuminuria was double compared to the preoperative albuminuria negative patients. The direct relationship between nature of operation and development of post-catheterization UTI was difficult to establish, because of the duration of catheterization acting as a confounding variable. Conclusion: In most cases of LUCS and hysterectomy, catheter-associated complications can be overcome by avoiding catheterization altogether. This can be better achieved by encouraging the patient to void their bladder immediately before surgery. In long and complicated operations, catheterization cannot be avoided but the postoperative duration of catheterization can be reduced to avoid complications. Moreover, preoperative optimization of comorbid status, hemoglobin status, albuminuria etc can bring forth a favourable outcome in terms of catheterassociated complications. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.696-702